A Medical Expert System for Tropical Diseases Diagnosis - NA, Ibiobu; ND , Nwiabu (International Journal of Computer Sciences and Engineering, 2019)
In Nigeria, tropical diseases such as Malaria and Typhoid are prevalent because of insects such as mosquitoes and flies, which are the common carriers of these diseases. Therefore, there is need for an expert system to help the inadequacy of the medical personnel in the diagnosis of these diseases. This paper presents the design of an expert system that aims at providing the patient with background for suitable diagnosis and treatments (Especially typhoid and malaria diseases). The system is able to give appropriate diagnosis and treatment for two diseases namely; typhoid and malaria. Fuzzy logic type 2 has proved to be the remarkable tool for building intelligent decision making for approximate reasoning that can appropriately handle both the uncertainties and imprecisions. The proposed methodology is composed of four stages: the first stage is receiving the symptoms from the patient, second stage, it uses information from the patient to make some analysis and investigation to improve correct decision in the diagnosis and the third stage, is performing diagnosis on patient according to information supplied by the patient (symptoms, analysis and investigation). The system was able to diagnose tropical diseases by the different symptoms using the fuzzy logic rule. The need to arrive at the most accurate medical diagnosis in a timely manner that reduces further complications is the main outcome of the system.